2018
DOI: 10.1002/maco.201810039
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of epoxy/basalt flakes anticorrosive coatings

Abstract: A new high performance environment‐friendly anticorrosive coating is prepared using solvent‐free epoxy resin as film‐forming agent and basalt flakes as main antirust fillers, respectively. The hardness, the adhesion strength, the alkali‐/acid‐resistance, the salt water resistance, and other properties of the coatings are tested. The influence of the addition of different amounts of basalt flakes on the microstructure and anticorrosive property are investigated by water absorption, electrochemical impedance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The impedance magnitude at the highest frequency determines the electrolyte resistance while the one at the lowest frequency represents the resistance to corrosion. [20,21] The former is regarded as unchanged while the latter changes greatly, as shown in Figure 5. More specifically, the impedance magnitude |Z| for sample S1 is larger than 10 4 Ω•cm 2 , which is greater than those for samples S5 and S1′.…”
Section: Analysis Of Eis Testsmentioning
confidence: 99%
“…The impedance magnitude at the highest frequency determines the electrolyte resistance while the one at the lowest frequency represents the resistance to corrosion. [20,21] The former is regarded as unchanged while the latter changes greatly, as shown in Figure 5. More specifically, the impedance magnitude |Z| for sample S1 is larger than 10 4 Ω•cm 2 , which is greater than those for samples S5 and S1′.…”
Section: Analysis Of Eis Testsmentioning
confidence: 99%
“…It is very important to protect metals and alloys from corrosion by organic coating. [1][2][3] Polyurethane (PU) and epoxy coatings are highly resistant to abrasion and corrosion and have good adhesion to substrates. PU is also widely used in the manufacturing and defense industries.…”
Section: Introductionmentioning
confidence: 99%
“…Broughton et al [6] found that GFs modified with aminosilane had higher stiffness and strength than GFs modified with titanate. Yan et al [7] studied the alkali/acid resistance of epoxy/basalt flake coatings and concluded that good chemical durability will improve the anticorrosive property of epoxy coatings.…”
Section: Introductionmentioning
confidence: 99%